Prosthetic Rehabilitation of a Patient with Alzheimers Disease Using a Combined Ball, Bar and Clip Retained Implant Supported Overdenture: A Case Report (Global Journal of Medical Research, 2017)
Alzheimer’s disease (AD) is a progressive degenerative disease that affects the cognitive skills of an individual. It is a type of dementia which causes difficulty in orientation, emotional instability, loss of abstract thinking, motor skills and personal care. The common clinical symptoms of the disease are aphasia (loss of the ability to use speech and language), apraxia (loss of ability to perform learned and familiar movements), visual agnosia (inability to recognize familiar visual stimuli) and memory disorders1. The individual affected with AD tend to have coated hairy tongue, angular cheilitis, ulcerations, caries, periodontitis and finally tooth loss due to poor oral hygiene maintenance2. Due to improper oral hygiene the patients affected by AD tend to lose their teeth and have difficulty in eating. Within a period of time due to reduced intake of food they suffer from weight loss and are highly prone to systemic diseases. Hence rehabilitating such patients is very important as it can help them in restoring the functional chewing abilities. This case report elaborates the rehabilitation of an Alzheimer’s Disease patient using implant supported over denture.